2006
DOI: 10.1016/j.engfracmech.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of residual stress in failure assessment procedure

Abstract: The effect of residual stress on component failure has been investigated using the distributions from current failure assessment procedures, and a residual stress profile simple to apply with less conservatism has been proposed for the weld geometries of T-plate and tubular T-joint. The Stress intensity factors (SIFs) in the two weld geometries under various types of loads have been calculated using the Green's function method. The Green's functions were determined not only for the T-plate but also for the tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 8 publications
(15 reference statements)
1
21
0
Order By: Relevance
“…In this work, the calculated residual SIFs are compared with those that are reported for a welded T‐plate of medium and high‐strength steels from Refs . It is to be emphasized that the fatigue life of the welded joint and the effect of residual stresses and weld geometry can be evaluated if the solutions of K res and K app are known.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, the calculated residual SIFs are compared with those that are reported for a welded T‐plate of medium and high‐strength steels from Refs . It is to be emphasized that the fatigue life of the welded joint and the effect of residual stresses and weld geometry can be evaluated if the solutions of K res and K app are known.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, there is no WF applied to a general structure . More recent researches have found the general WF expression that can be used to approximate WFs for a variety of geometrical crack configurations.…”
Section: Materials and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Weld residual stresses were induced on the specimen during the fabrication process [19,20]. However, it was shown that the residual stresses relaxed rapidly in high-temperature structures.…”
Section: Structural Specimenmentioning
confidence: 96%
“…Residual stress patterns in tubular T-joint were investigated by Lee et al [2]. Residual stress patterns in tubular T-joint were investigated by Lee et al [2].…”
Section: Residual Stress Patternsmentioning
confidence: 99%